A personificação como recurso persuasivo em campanhas de pets: um estudo da revista Cães e Cia - Martins, Sílvia Cristina Cópia Carrilho Silva (2014)
The present study aims to analyze the personification as persuasive appeal in advertising campaigns dedicated to Pets Shops (a shop specialized in products and services for pets). To this end, we selected 12graphic design pieces published in the Cães e Cia. Magazine, from January to December 2013. The primary focus of the research is on the discourse of advertising, and especially about his attempt to entice pet owners - highlights on the fact that the pet owners represent a significant portion of consumers that has grown substantially in recent years. In this sense, the research has an exploratory nature and employs documentary research and literature review. This study takes as instrument, articles, materials and advertisements published in specialized magazines, targeting the world of pets . Authors such as João Vicente Cegato Bertomeu, João A. Carrascoza, Vestergaard and Schroder and are used for the foundation of the main ideas that guide the study, however, the fundamental strategy lies in the fundamental review of the theories of embodiment; the theoretical path and image analysis of the selected graphic design pieces that depict the use of personification and the persuasive speech of advertising. In this sense, note that the research was guided by the collection and examination of graphic pieces that employ personification as textual and visual appeal, using instruments of communication studies for analysis. The analysis was based on theories that focus on temporal, cultural and behavioral relationships. The areas of phenomenology (here we use authors like Merleau-Ponty e Furlani and Bacchi), the proxemics (using ethologist and anthropologist Edward Hall) will translate the constraints of human perception filters in the act of production and reception advertising discourse, as well as other authors who also pass through these areas. It is noteworthy that the references of this research include data collected in magazines (veterinary or otherwise), such as the magazine of the newspaper Folha de S. Paulo, National Geographic and Galileo, as well as official sites like ABINPET (Brazilian Association of the Industry products for Pets), ANFALPET (National Association of Manufacturers of Food for Pets), since these publications are more updated than academic research (masters and doctorates) on the topic.